O CASO DE UMA INDÚSTRIA FRIGORÍFICO FRENTE AO PROCESSO DE ABASTECIMENTO - Sparemberger, Ariosto; Zamberlan, Luciano; Büttenbender, Pedro L.; Wagner, Adriano; Sausen, Jorge O.; Höfler, Cláudio E.; Oerlecke, Dênio; Elmo K.; Zamin, Marciela (Salão do Conhecimento, 2013)
Resumo